Penentuan Faktor – Faktor Berpengaruh Terhadap Kualitas Kuat Tekan Bata Ringan Dengan Metode Statistical Process Control (SPC) Dan Metode Taguchi - Bayu Arif Wicaksono; Wiwik Sulistiyowati (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2017)
PT.Viccon Modren Industries is a company engaged in the brick industry light . Problems often arise during the process of making light brick is a lightweight brick compressive strength is not in accordance with company standards for ˃3,50 N / mm² , so the quality is not optimal light brick . In an effort to overcome these problems , it is necessary to control the production of Online Quality Control with Statistical Process Control methods to identify the root of the problems that occur in the production of lightweight brick . Statistical tools in Statistical Process Control methods include check sheets , Pareto charts , cause-effect diagrams , and maps control p . Then the data Statistical Process Control is integrated with the Taguchi method as Offline Quality Control to be used as a parameter in determining the factors that have significant influence in the optimization of compressive strength of lightweight brick. Based on the research showed that the factors significantly influence the light brick compressive strength is the amount of cement and gypsum number . Combination level of the factors that resulted in the average value and variance of compressive strength of lightweight brick that is optimal is the same , namely the setting factor water volume at level 2 for 150 Liter ( A2 ) , factor the amount of silica sand on level 2 of 550 Kg ( B2 ), cement jumalah factor on level 3 of 350 Kg ( C3 ) , as well as gypsum julah factor on level 3 of 300 Kg ( D3 ).